(untitled) (Sustainability in Debate, 2020)
In the scope of urban space production, Brazilian urban policy, despite pointing out in its guidelines the struggle for the right to the city, seems indifferent to the impacts of real estate speculation on ecosystems. Given the context of the climate emergency, there is an urgent need to align urban and environmental policy for planning cities adapted to climate change. This work presents, based on spatial data from the recent deforestation of the city of João Pessoa, the legal and socioenvironmental characteristics of the urban expansion of the city and how the municipal urban and environmental policy has catalyzed processes of socioenvironmental injustice. It appears that planning and management are limited to following the trends signaled by the real estate market and that pressure ecosystems, especially in the southern portion of the municipality, and also that democratic arrangements are forged to make society’s role in defending ecosystems unfeasible.